2007
DOI: 10.1163/156853007x187081
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Animal Abuse: Is There a Connection?

Abstract: In recent years, school violence has become an issue of great concern among psychologists, educators, and law-enforcement officials. Th e purpose of the current study was to examine the relationship between bullying, victimization, and abuse of nonhuman animals. Th e study assessed bullying and victimization experiences, animal abuse, and attitudes toward animals within a sample of 185 college males. Results of the study highlighted the important distinction between males involved in single episodes of animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…This result supports the hypothesis advanced by Henry and Sanders (2007), who argued that a strong power orientation results in a utilitarian view of one's environment. This result supports the hypothesis advanced by Henry and Sanders (2007), who argued that a strong power orientation results in a utilitarian view of one's environment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result supports the hypothesis advanced by Henry and Sanders (2007), who argued that a strong power orientation results in a utilitarian view of one's environment. This result supports the hypothesis advanced by Henry and Sanders (2007), who argued that a strong power orientation results in a utilitarian view of one's environment.…”
Section: Discussionsupporting
confidence: 90%
“…Power is defined as the ability to cause other people to behave in a specific way (Bennett 1988). Henry and Sanders (2007) hypothesized that individual differences in power motives may be related to empathy and behavior toward animals. Bennett (1988) found that nPower was negatively correlated with perspective taking and concern for others' feelings, two dimensions that have been identified as components of empathy (Davis 1983).…”
mentioning
confidence: 99%
“…One notable exception is the Attitudes Toward the Treatment of Animals scäe (ATTAS) developed by Henry in 2004. Consisting of 26 items, the ATTAS assesses sensitivity to the maltreatment of animals and has been used successfully to assess relationships between animal cruelty and involvement in other antisocial behavior (Henry 2004); between observing and participating in animal cruelty (Henry 200H); between animal cruelty behaviors and attitudes and the tolerance for animal maltreatment (Henry 2004); and between bullying, victimization and nonhuman animal abuse (Henry and Sanders 2007) within college student samples. : Many of the previous studies which have addressed human-animal relationships have done so by utilizing the Animal Attitude Scale (AAS, e.g., Herzog, Betchart and Pittman 1991 ;Taylor and Signal 2004;.…”
mentioning
confidence: 99%
“…Further, Henry and Sanders (2007) demonstrated the link between children who abuse animals and bullying in school, which again shows the need for realization at school and in the home of the significance of children harming animals.…”
Section: Harm Towards Animalsmentioning
confidence: 97%